Hydrodynamics of bacteriophage migration along bacterial flagella - Katsamba, Panayiota; Lauga, Eric (My University, 2019)
Bacteriophage viruses, one of the most abundant entities in our planet, lack the ability to move independently. Instead, they crowd fluid environments in anticipation of a random encounter with a bacterium. Once they land on the cell body of their victim, they are able to eject their genetic material inside the host cell. Many phage species, however, first attach to the flagellar filaments of bacteria. Being immotile, these so-called flagellotropic phages still manage to reach the cell body for infection, and the process by which they move up the flagellar filament has intrigued the scientific community for decades. Berg and Anderson [Berg and Anderson, Nature (London) 245, 380 (1973)10.1038/245380a0] proposed the nut-and-bolt mechanism in which, similarly to a rotated nut that is able to move along a bolt, the phage wraps itself around a flagellar filament possessing helical grooves (due to the helical rows of flagellin molecules) and exploits the rotation of the flagellar filament in order to passively travel along it. One of the main pieces of evidence for this mechanism is the fact that immotile mutants of bacterial species such as Escherichia coli and Salmonella typhimurium equipped with straight, but rotating, flagellar filaments with a preserved helical groove structure are still infected by their relative phages. Using two distinct approaches to address the short-range interactions between phages and flagellar filaments, we provide here a first-principles theoretical model for the nut-and-bolt mechanism applicable to mutants possessing straight flagellar filaments. Our model is fully analytical, is able to predict the speed of translocation of a bacteriophage along a flagellar filament as a function of the geometry of both phage and bacterium, the rotation rate of the flagellar filament, and the handedness of the helical grooves, and is consistent with past experimental observations.
Keywords: Biological fluid dynamics; Biological movement; Biomechanics; Cell locomotion; Locomotion; Swimming